Vulnerability of regional crystalline rock aquifers to fluoride contamina tion: a case study from southern Sri Lanka - Rajasooriyar, L.D.; Hiscock, K.M.; Boelee, E. (Ponencia presentada en la conferencia internacional sobre agua subterranea y clima en África, Kampala, Uganda, 2008)
The estimated health impact of naturally occurring fluoride is considered to be more widespread than arsenic (WHO, 2004). From the known global distribution of endemic fluorosis, the most affected re gions are in arid to semi-arid climatic zones. Fluoride (F-) in its most common form is found in several geo logical environments including igneous, sedimentary and metamorphic rocks and leaching of F- into surface, soil and ground waters is the most common cause of fluoride endemics worldwide. This paper presents a groundwater pollution vulnerability assessment based on the detailed hydrochemical survey completed by Ra jasooriyar (2003) of the regional distribution of high-F- groundwaters in the Uda Walawe Basin in the dry zone of southern Sri Lanka. Fluoride in groundwater was found to be predominantly from a geological source, mainly fluorine-bearing silicate minerals such as biotite and hornblende. Specific hydrogeological conditions, mainly rock-water interactions and groundwater recharge and discharge patterns, were found to determine the vulnerability of groundwater to fluoride. The groundwater vulnerability is higher in areas where there is li mited recharge that promotes longer residence times and greater rock-water interaction. Of secondary impor tance is high evapotranspiration in the downstream catchment areas where F- is concentrated in shallow groundwaters, whereas in upstream areas F- concentrations are additionally controlled by dilution in those areas that have been developed under an irrigation scheme.